Understanding work and employment - Ackers, Peter (Oxford University Press, 2003)
This book aims to analyze, advertise and criticize the contribution of industrial relations to social science understanding. It brings together leading scholars to reconsider the theoretical foundations of industrial relations and its potential contribution to the wider understanding of work and economic life, to learn what it can gain from a stronger engagement with these surrounding disciplines and national traditions.The introduction provides a critical, though broadly sympathetic outline of the development of the main stream industrial relations tradition. Part One recognizes the interdisciplinary character of industrial relations by concentrating on 'border encounters' with the cognate academic disciplines of sociology, economics, management, history, psychology, law, politics and geography